Wireless transceiver bit error rate and capacity improvement using advanced decoding techniques - Ahmed Mohammed Ahmed; Wurod Qasim Mohamed; Israa Hazem Ali (Bulletin of Electrical Engineering and Informatics, 2022)
This paper considers advanced techniques for multiple-input multiple-output (MIMO) detection and decoding techniques to improve bit error rate (BER) and channel capacity. These are requirements for sixth generation (6G) (the next generation) access networks. A parallel decoding and detection scheme and a soft bit decoding scheme are implemented meregely to boost the overall performance of MIMO communication systems. The proposed new system is called the advanced system which comprises the two mentioned advanced techniques of decoding. For simplicity, these advanced techniques are employed and developed using two antennas at both ends, transmitter, and receiver. Then it is compared with the other different techniques which are spatial multiplexing SM–sequential decoding zero forcing-interference cancelation (ZF-IC) technique and SM–parallel decoding technique. We show that the advanced system outperforms the other two mentioned systems by achieving ultra-reliability and a high capacity simultaneously without employing space time coding and error control coding techniques. Additionally, better BER performance is achieved with less resolution and the quantization error reduced with an increasing the resolution. The new advanced system is simulated and evaluated with three terms, channel capacity, BER, and quantization error.